AB0027 Tnf-alfa responses induced by different enterobacteria and gram-positive cell walls of normal intestinal microbiota in early rheumatoid arthritis. (1st June 2001) - Luukkainen, RK; Cheng, T; Rimpiläinen, M; Möttönen, T; Yli-Kerttula, U; Saario, R; Toivanen, P
Abstract : Background: The aetiology of the rheumatoid arthritis (RA) is unknown. A variety of infective agents have been proposed to be the etiological factor of the disease. Objectives: To study whether enterobacteria and Gram-positive bacterial cell walls (BCW) derived from normal intestinal microbiata are involved in the etiopathogenesis of early rheumatoid arthritis. Methods: Peripheral blood mononuclear cells (PBMC) and synovial fluid mononuclear cells (SFMC) were isolated from patients with early RA (the average duration of 3 months). The tumour necrosis factor-alpha (TNF-alfa) responses to heat-killed Salmonella enteritidis, Yersinia enterocolitica and Escherichia coli, and to Gram-positive BCW derived from four common intestinal indigenous bacteria, Eubacterium aerofaciens, Eubacterium limosum, Lactobacillus casei and Lactobacillus fermentum, and a BCW derived from a pathogen, Streptococcus pyogenes were investigated. Results: The results obtained indicate that these bacterial antigens induce TNF-alfa responses of PBMC and SFMC from at least some patients with early RA. However, the responses are not spesific for any particular bacterial antigen tested. The responses observed are similar to those observed in the patients with other inflammatory arthritides. Conclusion: These results suggest that SFMC reacting with BCW exist in some patients with early RA. They are in agreement with the hypothesis that BCW derived from normal intestinal microbiota might be involved in the etiopathogenesis of chronic arthritides, including RA.